O novo tipo penal de estupro: art. 213 do CP e a problemática do concurso de crimes - Silva, Maurício Pereira da (2012)
This study proposes to analyze the new type of criminal problem of rape and crimes contest inserted in art. 213 of the Criminal Code, according to Law no. 12015 of 07 August 2009. This united and equated the offense of indecent assault to rape criminal figure. Ready emerged from studies and debates about the aforementioned legislative innovation, which some refer to the new criminal offense of rape as an alternative mixed type, and others say is a mixed type cumulative. So the question: is the applicable contest crimes in the new type of criminal offense of rape? If applicable, what kind should be applied to the liability of the agent? It is noteworthy that prior to the Act, the key to the consummation of the crime of rape was human conduct to practice "carnal knowledge", we can state categorically that this would be the only action capable of setting up the offense. With respect to the consummation of the offense that was the crime of "gross indecency", the making of any lewd acts in order to satisfy lust, carnal knowledge of diversity, would characterize. So, assuming consummation of the two crimes on the same factual context, the impasse was resolved with foundation material of crimes in the contest. However, with the current wording, the problem lies in ebolição. Therefore, the study of the two institutes, type of rape and crimes contest, becomes relevant because, depending on the position adopted will reflect the application of the sentence considerably. According to the legislative change of the Penal Code, find interesting, or at least try to present a solution that brings soothing more legal certainty, therefore, doctrine and jurisprudence are not in unison on the issue. Thus, this paper aims to examine the issue, considering the application of the contest to the crime of rape crimes, and if possible such application, point the species being used to hold the criminal agent: the "material contract", the "formal tender "or" continuing criminal offense. " In order to conduct the job well and reach a conclusion in accordance with the pre-existing ideas, researched and foreign doctrinal works, and jurisprudence, due to the construction of logical reasoning. We consider unacceptable the application of the competition material by treating crimes are the two typical figures provided in art. 213 for a single crime - rape. In the extreme case, apply the continuity institute criminal offense because it is not up to the operator's right, at least in criminal matters, fix a technical failure of the legislature, without infringing the fundamental principle is that of legality. Accordingly, the legislature recognizes that criminal failed badly, so much so that the design of the new Penal Code separates again the figures typical of rape and indecent assault, and ends with the term "carnal knowledge" that brings so many interpretive questions in practice. Thus, the new legal text dealing with the crime of rape discriminates explicitly the term "vaginal conjunction", integrating also the terms "conjunction anal" and "oral"